Propuesta de articulación urbano arquitectónica entre el espacio público de los establecimientos penitenciarios y su contexto inmediato en el Valle del Cauca. - Arciniegas Dorado, Daniela; Mosquera Peralta, Cristian Alejandro (Universidad Antonio Nariño, 2021)
ABSTRACT The concept of exclusion is very usual in the field of the political social sciences to refer to the social situation unfavorable of a person or a group of individuals. In this sense, it this expected that an economic system or a country model favors social integration and general welfare those who don’t enjoy development opportunities or who fail to meet their basic needs, which are considered a focus of pollution for the city. Obviously, the prison is one of the institutional spaces designed to segregate and exclude, this is determined because society is responsible for classifying and pointing out these facilities due to the social condition of the inmates, generating an insecurity in the immediate context. It is for this reason that (USPEC, 2017) ¨ Unidad de Servicios penitenciarios y carcelarios ¨ is responsible for generating guidelines for the construction of this type of prison facilities; justifying that it must have a determined insulation from the jail to generate a nonexistent integration between the public space of prison and prison facilities in the Valle del Cauca with the immediate context, achieving the creation of criteria for revitalization, which articulate these two urban elements.